Improving Teacher Professionalism Through Academic Supervision - Poniman Poniman; Hakima Maris; Undang Rosidin; Sowiyah Sowiyah; Hasan Hariri (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2025)
Abstract: This study aims to comprehensively describe the role of academic supervision in improving teacher professionalism at Sekolah Menengah Kejuruan Negeri (SMKN) in Mesuji District, Lampung Province. The research was conducted using a quantitative approach with survey methods to measure the level of influence between the two variables. The population consisted of 173 teachers from various SMKNs in the district, and a sample of 120 teachers was determined using the Taro Yamane formula with proportional random sampling. Data were collected through a structured questionnaire that assessed indicators of academic supervision—such as planning, implementation, follow-up, and feedback—and aspects of teacher professionalism, including pedagogical competence, discipline, innovation, and responsibility. The collected data were analyzed using prerequisite tests and hypothesis testing through regression analysis. The results reveal that academic supervision has a positive and significant effect on improving teacher professionalism. Effective supervision encourages teachers to reflect on their teaching practices, develop creative learning strategies, and maintain continuous professional growth. Therefore, consistent and constructive academic supervision can be considered a key managerial function for enhancing teacher performance, instructional quality, and ultimately, the overall effectiveness of vocational education in Mesuji District, Lampung. Keyword: Academic Supervision, Teacher Professionalism.